Shape Setting in super-elastic NiTi ribbon. (December 2018) - Samal, S; de Prado, E.; Tyc, O.; Sittner, P.
Abstract: The various application of shape memory alloys requires setting of NiTi ribbon in particular form. Shape setting is accomplished by constraining the NiTi ribbon on a mandrel that undergoes heat treatment. Surface annealing of super-elastic NiTi ribbon was performed shape inside the furnace. The duration of furnace temperature was kept fixed for 2 h. The sample was held in bend position for annealing the martensitic phase created on the surface of NiTi ribbon. The aim is to anneal the martensitic phase on the upper surface region and introduce the compressive stress on the edge of the alloy. The induced surface strain determines the volume fraction of martensitic formed on the sample in the flat position at room temperature. The shifting of the peak and evolution of new peaks as function of the temperature on the annealed NiTi ribbon at the flat position was observed. X-ray diffraction was carried out on the shape set bended sample at room temperature and constrained flat position (both outer and inner surface). The bended NiTi ribbon annealed at 350° C shows a mixture of austenitic phase and plastic deformation region that confirms from the broadening of some peaks. The residual stress arises from the plastically induced periphery region and the elastic core region that allows the NiTi ribbon returns partially to original flat shape. However, fully shape set was achieved on super-elastic NiTi ribbon annealed at 400 and 450 °C.